2020
DOI: 10.1016/j.ebiom.2020.102846
|View full text |Cite
|
Sign up to set email alerts
|

Fucosyltransferase 4 shapes oncogenic glycoproteome to drive metastasis of lung adenocarcinoma

Abstract: Background Aberrant fucosylation plays a critical role in lung cancer progression. Nevertheless, the key fucosyltransferase with prognostic significance in lung cancer patients, the enzyme's intracellular targets, and complex molecular mechanisms underlying lung cancer metastasis remain incompletely understood. Methods We performed a large-scale transcriptome-clinical correlation to identify major fucosyltransferases with significant prognostic values. Invasion, migrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…FUT4 is a key enzyme in the oligosaccharide synthesis of LEY (32). Recent studies have reported that FUT4 drives the metastasis of lung adenocarcinomas (33), and FUT4 overexpression is accompanied by EMT in breast cancer cells (34). In the current study, autophagic TAMs increased FUT4 expression.…”
Section: Discussionsupporting
confidence: 59%
“…FUT4 is a key enzyme in the oligosaccharide synthesis of LEY (32). Recent studies have reported that FUT4 drives the metastasis of lung adenocarcinomas (33), and FUT4 overexpression is accompanied by EMT in breast cancer cells (34). In the current study, autophagic TAMs increased FUT4 expression.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, the addition of another LacNAc creates a sialyl-dimeric Le X/A antigen O -glycan which is also specifically found in cancer ( Figure 1 F ). The fucosyltransferase FUT4 involved in the biosynthesis of sLe X antigen is overexpressed in colon cancer ( Figure S16 ) and it was previously associated with lung adenocarcinoma metastasis and poor patient prognosis 50 , 51 . It was also previously described that the upregulation of sLe X/A antigens in CRC is due to downregulation of B4GALNT2.…”
Section: Resultsmentioning
confidence: 99%
“…FUT3 is involved in tumorigenesis, proliferation, and migration of pancreatic cancer [ 41 ]. FUT4 is correlated with higher metastatic potentials in lung cancer [ 42 ]. FUT6 is associated with metastatic colorectal cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%